Dynamic of Friction Coupling Independently Rotating Wheels for High Speed - Yan Shi; Miao Li; Weihua Ma; Kang Chen (Shock and Vibration)
A new lateral coupling structure with independently rotating wheels (IRW) is proposed, and longitudinal creepage is obtained by replacing the gear pair with the friction pair to synchronize the rotation speed of left and right wheels. The auxiliary wheelset made up of two friction wheels can be placed either under the primary suspension or on the frame. Vehicles dynamics models with three different kinds of bogies are developed, including friction coupling bogie with independently rotating wheels (FCIRW-bogie), bogie with independently rotating wheels (IRW-bogie), and bogie with rigid wheelsets, and their guiding and resetting capability when negotiating large-radius curves are compared and analyzed. Results show that FCIRW has the advantages of both IRW and rigid wheelset. On the straight track, FCIRW has sufficient wheel-rail longitudinal creep force to assist the reset; its critical speed is much higher than that of the rigid wheelset. On the curved track, the whole vehicle wear power of FCIRW-bogie vehicle is about 2/3 of the rigid axle level.